2015
DOI: 10.1021/acs.jafc.5b03462
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma atrum Polysaccharide Ameliorates Hyperglycemia-Induced Endothelial Cell Death via a Mitochondria-ROS Pathway

Abstract: The aim of the present study was to examine the role of Ganoderma atrum polysaccharide (PSG-1) in reactive oxygen species (ROS) generation and mitochondrial function in hyperglycemia-induced angiopathy. In this work, ROS scavenger, oxidizing agent tert-butylhydroperoxide (tBH), mitochondrial permeability transition pore (mPTP) blockers, and caspase inhibition are used to investigate whether PSG-1 may promote survival of human umbilical vein cells (HUVECs) through preventing the overproduction of ROS and mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…The mitochondria are a major source of ROS, which is particularly susceptible to oxidative stress . Previous studies have shown that Astragalus and Cornus polysacharides inhibits mitochondrial injury caused by the continuous production of free radicals and selective oxidative damage , and Ganoderma atrum polysacharides protect mitochondrial by scavenging ROS , increasing the activity of antioxidant enzymes, and Astragalus and ginseng polysacharides ameliorating mitochondrial dysfunction, which ultimately improved energy metabolism . In the present study, we found that palmitate‐treated HepG2 cells showed marked changes in several parameters of the mitochondrial function (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The mitochondria are a major source of ROS, which is particularly susceptible to oxidative stress . Previous studies have shown that Astragalus and Cornus polysacharides inhibits mitochondrial injury caused by the continuous production of free radicals and selective oxidative damage , and Ganoderma atrum polysacharides protect mitochondrial by scavenging ROS , increasing the activity of antioxidant enzymes, and Astragalus and ginseng polysacharides ameliorating mitochondrial dysfunction, which ultimately improved energy metabolism . In the present study, we found that palmitate‐treated HepG2 cells showed marked changes in several parameters of the mitochondrial function (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…There are mounting evidences that HFD‐induced oxidative stress resulting from the overproduction of ROS is a major factor contributing to the development and progression of liver damage. The collapse of the MMP results in the rapid release of cytochrome C into the cytoplasm . In the present study, palmitate‐treated HepG2 cells showed a marked increased generation of mitochondrial ROS (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Cui et al [38] studied the protective effect of sulfated polysaccharide (such as SJP) against 6-OHDA-induced SH-SY5Y cell death and found that the Δ Ψ m of SJP pretreatment group (79%) was higher than 6-OHDA damaged group (56%), suggesting that SJP had certain protective effect on 6-OHDA-induced SH-SY5Y cell damage. Li et al [39] examined the endothelial cell death mode caused by high glucose-induced ROS and suggested that Ganoderma atrum polysaccharide (PSG-1) had protective effect on the Δ Ψ m. The Δ Ψ m (36.26%) of high glucose-treated group was obviously lower than the cell of the control group (80.44%), but the Δ Ψ m increased (60.03%) after the cells were pretreated by PSG-1.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [39] examined the high glucose-induced ROS production and cell apoptosis of endothelial cells and suggested that the cell apoptotic rate of high glucose treatment group was 20.66%, whereas the cell apoptotic rate reduced to 12.68% after the cells were pretreated with PSG-1, which indicated that PSG-1 can alleviate cell apoptosis induced by oxidative stress. Similarly, Chowdhury et al [49] revealed that the bacterial fucoidan can inhibit the H 2 O 2 -induced stress of human lung fibroblasts, and the total cell apoptotic rate of H 2 O 2 -damaged group and polysaccharide repair group was 42.6% and 10.0%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…ROS include superoxide anion (O 2 ˙ − ), peroxynitrite (ONOO − ), nitric oxide (NO), hydrogen peroxide (H 2 O 2 ) and hydroxyl radical (·OH) . Although normal ROS regulation is crucial for cellular functions , aberrant production of ROS is related to many diseases , such as Alzheimer's disease , Parkinson's disease , diabetes , cancer , etc. Note that O 2 ˙ − is one of the major ROS due to its highly oxidative activity.…”
Section: Introductionmentioning
confidence: 99%